CYCLONES OVER THE PACIFIC OCEAN AND FAR-EASTERN SEAS IN COLD AND WARM SEASONS AND THEIR INFLUENCE ON WIND AND THERMAL REGIME IN THE LAST TWO DECADE PERIOD - S. Yu. Glebova (Известия ТИНРО, 2018)
Cyclonic activity in the Asia-Pacific region is largely determined by state of the seasonal centers of atmosphere action. In turn, cyclones themselves influence on conditions in certain «key» areas. Recently the Aleutian Low activity declines in fall-winter and this center is shifted westward, but activity of the Hawaiian High increases in warm season. As the result, heightened air pressure prevails over the Ocean (positive anomalies of the sea level pressure) and lowered pressure (negative anomalies) — over the Far Eastern Seas. In this anomalous situation, the number of cyclones over the Ocean has increased but they become weaker that causes SST increasing in the North Pacific both in winter and summer. Over the Bering Sea, the cyclones become weaker, as well, but this regime causes the ice cover increasing, so SST decreasing in spring. On the contrary, over the Okhotsk Sea and Kuril Islands area, the number of cyclones has decreased gradually but they become stronger in both seasons that causes the ice cover reducing and spring SST rising. In the Japan Sea, cyclonic activity has intensified, too, but this tendency causes cooling in winter and warming in summer.